2018
DOI: 10.1107/s2056989018006473
|View full text |Cite
|
Sign up to set email alerts
|

RbFe(HAsO4)2 and TlFe(HAsO4)2, two new hydrogenarsenates adopting two closely related structure types

Abstract: Rubidium iron bis­[hydrogen arsenate(V)] and thallium iron bis­[hydrogen arsenate(V)] were grown under mild hydro­thermal conditions (T = 493 K, 7 d). RbFe(HAsO4)2 adopts the RbFe(HPO4)2 structure type (space group R c), while TlFe(HAsO4)2 crystallizes in the (NH4)Fe(HPO4)2 structure type (space group P ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The three structure types are very closely related to each other and are modifications of a basic tetrahedral-octahedral framework structure containing microporous interpenetrating channels, which host the M + cations. The three structure types, among which only the RbFe(HPO 4 ) 2 -type (Lii & Wu, 1994) was described before, are also related to the triclinic (NH 4 )Fe(HPO 4 ) 2 -type (Yakubovich, 1993), with CsSc(HAsO 4 ) 2 (Schwendtner & Kolitsch, 2004b), (NH 4 )Fe(HAsO 4 ) 2 (Ouerfelli et al, 2014) and TlFe(HAsO 4 ) 2 (Schwendtner & Kolitsch, 2018) as arsenate members. The general building unit in all these structure types contains M 3+ O 6 octahedra which are connected via their six corners to six protonated AsO 4 tetrahedra (M 3+ As 6 O 24 group).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The three structure types are very closely related to each other and are modifications of a basic tetrahedral-octahedral framework structure containing microporous interpenetrating channels, which host the M + cations. The three structure types, among which only the RbFe(HPO 4 ) 2 -type (Lii & Wu, 1994) was described before, are also related to the triclinic (NH 4 )Fe(HPO 4 ) 2 -type (Yakubovich, 1993), with CsSc(HAsO 4 ) 2 (Schwendtner & Kolitsch, 2004b), (NH 4 )Fe(HAsO 4 ) 2 (Ouerfelli et al, 2014) and TlFe(HAsO 4 ) 2 (Schwendtner & Kolitsch, 2018) as arsenate members. The general building unit in all these structure types contains M 3+ O 6 octahedra which are connected via their six corners to six protonated AsO 4 tetrahedra (M 3+ As 6 O 24 group).…”
Section: Resultsmentioning
confidence: 96%
“…Among the many different structure types found during that study, one atomic arrangement, the RbFe(HPO 4 ) 2 -type (Lii & Wu, 1994), was found to be extremely versatile and allowed the incorporation of a wide variety of cations. Two new representatives of this structure type, which was previously also known for RbM 3+ (HPO 4 ) 2 (M 3+ = Al, Ga; Lesage et al, 2007), M + In(HAsO 4 ) 2 (M + = Rb, Cs; Schwendtner & Kolitsch, 2017d) and RbFe(HAsO 4 ) 2 (Schwendtner & Kolitsch, 2018), are presented in this study, namely RbAl(HAsO 4 ) 2 and CsFe(HAsO 4 ) 2 . Two chemically identical compounds, crystallizing in the space group R32, represent a novel but closely related structure type.…”
Section: Introductionmentioning
confidence: 77%
“…There exist only three other Cs-Ga arsenates: The structurally closely related CsGa 2 As(HAsO 4 ) 6 (Schwendtner & Kolitsch, 2018b), in which one third of the M 3+ O 6 octahedra are replaced by AsO 6 octahedra; CsGa(H 2 AsO 4 )(H 1.5 AsO 4 ) 2 (Schwendtner & Kolitsch, 2005) which was encountered in the same synthesis batch as the title compound; and Cs 2 Ga 3 (As 3 O 10 )(AsO 4 ) 2 (Lin & Lii, 1996).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The three title compounds are isotypic and new representatives of the RbAl 2 As(HAsO 4 ) 6 -structure type (R3c; Schwendtner & Kolitsch, 2018a), which is a recently described variation of the RbFe(HPO 4 ) 2 structure type (R3c; Lii & Wu, 1994) and closely related to the following two structure types: (NH 4 )Fe(HPO 4 ) 2 (P1; Yakubovich, 1993) and RbAl(HAsO 4 ) 2 (R32; Schwendtner & Kolitsch, 2018a). The reader is referred to our latest papers for a detailed discussion of the four related structure types (Schwendtner & Kolitsch, 2018a) and a review of compounds crystallizing in the RbFe(HPO 4 ) 2 and (NH 4 )Fe(HPO 4 ) 2 structure types (Schwendtner & Kolitsch, 2018b). All of these modifications share a basic tetrahedraloctahedral framework structure featuring interpenetrating channels, which host the M + cations (Figs.…”
Section: Structural Commentarymentioning
confidence: 99%
“…As a result of the smaller ionic radius of As 5+ this substitution also has an effect on the unit-cell parameters (Table 3) and the pore diameter. While the lengths of the c axis of all so far known RbFe(HPO 4 ) 2 -type arsenates range from 52.87 (1) to 56.99 (1) Å (Schwendtner and Kolitsch, 2018b) and correlate well with the sizes of the involved M + and M 3+ cations, the length of this axis in the RbAl 2 As(HAsO 4 ) 6 -type compounds is much smaller and the range of lengths much narrower [50.17 (1)-50.94 (1) Å , see Table 1]. The c unit-cell parameter correlates with the size of the involved M 3+ cation, while the M + cations seem to show a negative correlation with the c parameter ( Table 1).…”
Section: Figurementioning
confidence: 99%